Effects of call centers on the community - Mata, Marlon Julius; Jaco, Jireh; Pulo, Mary Grace; Sayat, Joy; Secugal, Jolly Mae; Toledanes, ma. theresa
This research study was conducted on the 5th day of September 2007. It aimed to determine the reasons for Call Centers to sprout in Iloilo City, to discuss whether there are business and industries that directly benefit from the establishment of Call centers and to describe the effect of Call Centers on the community, especially on its social, moral, economic aspects and the land use. The research study utilized 42 residents of Brgy. Inday, 78 residents from Brgy. Taal, 70 residents from Brgy. Tap-oc and 72 residents from Brgy. North San Jose. These are the barangays surrounding Ventus and Callbox; the two most established Call Centers in Iloilo City. Data were gathered through the use of survey questions for the different effects of call Centers on the community. The data was analyzed by using the simple arithmetic and easy to draw pictures to summarize the data and the probability theory to answer specific questions. results reveal that Call Centers does not affect the community that much.